Robodog / Ahmad Syamil Ahamad Sabirin ...[et al.] - Ahamad Sabirin, Ahmad Syamil; Saipol, Mohamad Amirul Azri; Mohd Arif, Mohamad Syafiq; Mohd Rosli, Ahmad Zahid; Suhaimi, Mohd Aideed Firdausy (2016)
Home, the place where we live, sleep, eat, bathe, cook and having quality time with friends and family. But, with lack of security, house that we live are exposed to the intruders, robbers or thieves. So, the team would like to introduce our new innovation for security home system, the 'RoboDog'. This 'RoboDog' is installed with several features such as Iridium Metal for the whole body of the 'Robodog', six cameras 13MP with night vision. Stereo speaker to produce barking sound, GPS tracking to track position of 'RoboDog', long lasting battery for eight hours, motion sensor to detect the movement of burglary and users can also retrieve information transferred by 'RoboDog' through a mobile application.